Management of Village Funds for Development in Serang District (Case Study in Teluk Terate Village) - Chaidir, John (PINISI Discretion Review, 2022)
This research is to discuss the exiting conditions of the management implementation of public policies in Government of Serang Regency in the Village Fund program which at this time is being actively disbursed by the Central Government through local regency government. The research in this thesis is qualitative research which means that the primary data from this study is obtained by relying on in-depth interviews with several key informants until the data becomes saturated and explores opinions through Focus Group Discussion. The key informants from this study consisted of Serang Regent, leading sector and supporting sector in Serang Regency Government, as well as operational sectors of Village Fund activities such as Village Heads and Village Facilitators. This research was conducted in Teluk Terate Village, Kramatwatu District, Serang Regency. The writing of this paper is also carried out with reference sources from various literatures which are equipped with a subjective review of the researcher on the topic presented. From the results of the study, there were some constraints in the management of the Village Fund in general, such as the existence of a three-sectoral ego that handled Village Government, the paradox of Village Fund regulation policies, too many regulations issued, the lack of professionalism of Village Assistance, and several other obstacles. This study obtained the ideal model and ideal strategy for management implementing of the Serang Regency Government in handling the Village Fund. In carrying out a description of the implementation of the Serang Regency Government policy on the Village Fund, researchers used the approach through the theory of Edward III.